Comparison of design features of quadrotor aircraft and helicopters from the point of view of flight - Han, D.; Barakos, G.N. (My University, 2021)
Blade flapping, control methods and rotor/rotor aerodynamic interference are some of the main differences between quadrotor aircraft and helicopters. To investigate these differences in flight performance of square formation quadrotor aircraft, a performance prediction model, including a validated rotor model, an aerodynamic model, and a propulsive trim model, is used. The square formation quadrotor aircraft with variable blade pitch or rotor speed as control means are analyzed. Compared with a helicopter rotor, from low to medium speed flight, the aerodynamic interference between the front and rear rotors dominates the power difference between quadrotors and helicopters. At high speed flight, the blade flapping and aerodynamic interference can lead to increased power, and the blade flapping can be more pronounced. Applying cyclic pitch controls in quadrotor aircraft can effectively control the blade flapping, reduce the rotor power, and increase the maximum forward speed. In general, the overall rotor power consumption of quadrotor aircraft is larger than the equivalent helicopter rotor.